2022
DOI: 10.1021/acschembio.1c00856
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into the Reaction Mechanism of Ketosynthase-Like Decarboxylase in a Loading Module of Modular Polyketide Synthases

Abstract: Ketosynthase-like decarboxylase (KSQ) domains are widely distributed in the loading modules of modular polyketide synthases (PKSs) and are proposed to catalyze the decarboxylation of a malonyl or methylmalonyl unit for the construction of the PKS starter unit. KSQ domains have high sequence similarity to ketosynthase (KS) domains, which catalyze transacylation and decarboxylative condensation in polyketide and fatty acid biosynthesis, except that the catalytic Cys residue of KS domains is replaced by Gln in KS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
5
20
0
1
Order By: Relevance
“…This network might assist the decarboxylation of malonyl-ACP by providing such a water molecule needed for bicarbonate formation, as well as for accommodating the bicarbonate product. This observation supports the bicarbonate-forming mechanism, as opposed to the mechanism that posits release of carbon dioxide (Chisuga et al ., 2022). More biochemical and structural studies are required to definitively address this long-standing question (Heil et al ., 2019).…”
Section: Resultssupporting
confidence: 79%
“…This network might assist the decarboxylation of malonyl-ACP by providing such a water molecule needed for bicarbonate formation, as well as for accommodating the bicarbonate product. This observation supports the bicarbonate-forming mechanism, as opposed to the mechanism that posits release of carbon dioxide (Chisuga et al ., 2022). More biochemical and structural studies are required to definitively address this long-standing question (Heil et al ., 2019).…”
Section: Resultssupporting
confidence: 79%
“…We expected that in vitro analysis of the transacylation reaction of the VinP2 KS 4 domain is suitable for evaluation of the protein‐protein recognition involved in the intermodular transacylation reaction between polypeptides. We expressed recombinant VinP2 NDD 4 KS 4 protein that contained the neighboring AT 4 domain (Met1‐Gly931) in Escherichia coli because it was reported that type I PKS KS recombinant protein expressed as a single domain is often obtained as an insoluble form [11,12] . To exclude the effect of the VinP2 AT 4 domain, we prepared the VinP2 NDD 4 KS 4 AT 4 S684G mutant in which the catalytic Ser684 residue of the AT 4 domain was mutated.…”
Section: Resultsmentioning
confidence: 99%
“…The vinP1 ACP 3 CDD 3 fragment was amplified by PCR using cosmid K1B10 as the template DNA with the oligonucleotides shown in Table S5. The amplified fragment was cloned into the expression vector pColdW (modified vector derived from pColdI) [12] using Nde I and Xho I restriction sites to form pColdW‐ vinP1 ACP 3 CDD 3 . For the expression of the VinP1 ACP 3 CDD 3 , E. coli BL21(DE3) (Nippon Gene Co., Ltd.) cells harboring pColdW‐ vinP1 ACP 3 CDD 3 were grown at 37 °C in LB broth containing ampicillin (50 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This network might assist the decarboxylation of malonyl-ACP by providing the water molecule needed for bicarbonate formation, as well as by accommodating the bicarbonate product. This observation would support the bicarbonate-forming mechanism, as opposed to the mechanism that posits the release of carbon dioxide (Chisuga et al, 2022). Further biochemical and structural studies are required to definitively address this longstanding question (Heil et al, 2019).…”
Section: The Implication Of the Side Pocket In The Ks Mechanismmentioning
confidence: 91%